Pengaruh Lingkungan Kerja dan Kepuasan Kerja terhadap Kinerja Karyawan PT Sanco Indonesia - Pamungkas, Triadi; Hendra Galuh Febrianto (Institut Penelitian Matematika Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to determine the influence of work environment and job satisfaction on employee performance at PT. Sanco Indonesia. The limitations in this study are that the variables used in this study are Work Environment (X1) and Job Satisfaction (X2) as independent variables and Employee Performance (Y) as bound variables. PT Sanco Indonesia provides support in thesis research by providing access to data, employee participation as respondents, and insights from management related to work environment policies and job satisfaction. This research is a quantitative research and survey research. In this study, a type of probability sampling was used with a simple random sampling technique. The sample in this study amounted to 89 employees and the object in this study was PT. Sanco Indonesia. The data collection technique is through the distribution of questionnaires, the data obtained in the analysis uses the PLS (Partial Least Square) technique through Smart PLS software. The results of this study show that partially the variable Work Environment (X1) has a positive and significant effect on employee performance (Y), Job Satisfaction (X2) has a positive and significant effect on employee performance (Y) at PT. Sanco Indonesia. Keywords: Employee Performance, Job Satisfaction, Work Environment.